Influence of carrier effect on Pd/Al2O3 for methane complete catalytic oxidation - Peng, Shengpan; Ma, Ziran; Ma, Jing; Wang, Hongyan; Chen, Jingyun; Wei, Hui; Li, Yonglong; Ao, Zhimin; Wang, Baodong (Frontiers in Chemistry, 2022)
Pd/Al2O3 catalysts modified by different chemical elements (Mg, Si, Ce, Zr) were studied for methane (CH4) catalytic combustion. The carrier effects of Pd/Al2O3 and acid strength influences on CH4 oxidation were assessed in detail. Pd 3d binding energies (BE) could alter the activation energy of CH4 combustion. Furthermore, the acidity of support affects the pre-exponential variables (A). When the BE of Pd 3d5/2 is 337.3 eV, PdO nanoparticles loaded on modified Al2O3 exhibit outstanding activity in shattering the C-H bond, resulting in the lowest activation energy (Ea), regardless of the PdO nanoparticle size effect. Furthermore, a proposed theory explains that acid sites on catalysts boost the elementary step (2PdOH PdO* + Pd* + H2O) and the pre-exponential variables rely on the amount of exposed Pd* and PdO*. As a result, the Al2O3 carrier not only alters the electrical properties and nanoparticle size of the supported PdO but also participates in the reaction process via acid sites on the Al2O3 surface.